Carcass Traits and Blood Biochemistry of Broiler Birds Fed Betaine Hydrochloride Supplemented Diets - Shubhnish; Sihag, Sajjan; Kumar, Sushil; Bai, Radha; Komal (Indian Journal of Animal Nutrition, 2025)
A study was conducted to assess the effect of different levels of betaine hydrochloride on the carcass characteristics and different blood biochemical parameters of broiler chicken. A total of 200 birds were allocated five different treatment groups of which T1 was taken as control while T2, T3, T4, and T5 were fed diet supplemented with 500, 1000, 1500 and 2000 mg/kg basal feed betaine hydrochloride, respectively. The percentage dressed, eviscerated and drawn carcass weight were significantly (P